Treatment and visual prognosis in Behçet's disease. Issue 8 (August 1986) - Benezra, D; Cohen, E
Abstract : For the last decade we have observed and regularly followed 49 patients with the ocular type of Behçet's disease. Thirty-six patients were males and 13 were females. Regardless of whether the initial ocular presenting symptoms were in the anterior or posterior segment, both segments were involved within two years. Sterile hypopyon was recorded in 17 out of the 49 patients during the process of follow-up. In three of the patients hypopyon was the presenting symptom. Characteristically there was a lack of corneal or scleral involvement in the disease process. All patients responded initially to treatment with steroids, but 42 had a course of treatment with cytotoxic-immunosuppressive drugs for various lengths of time after 'resistance' to steroids developed. Although definitely effective in reducing the intensity of the ocular inflammatory processes, it is not clear yet whether these modes of treatment have any dramatic effect of the visual prognosis of the affected eyes. Despite intensive follow-up and treatment, loss of useful visual acuity has occurred in 74% of the eyes six to 10 years after the start of the ocular symptoms.